When Prussian Blue Meets Porous Gold Nanoparticles: A High Signal‐to‐Background Surface‐Enhanced Raman Scattering Probe for Cellular Biomarker Imaging. Issue 7 (30th May 2019) - Li, Xuejing; Zeng, Erzao; Di, Huixia; Li, Qiang; Ji, Jingwei; Yang, Jie; Liu, Dingbin
Abstract: Profiling cellular biomarkers without the interference of endogenous signals could facilitate the investigation of complex intracellular biological events and provide new possibilities for precision disease diagnosis. Herein, a surface‐enhanced Raman scattering (SERS) probe with a high signal‐to‐background ratio (SBR) for cellular biomarker imaging is constructed. The probes are prepared by incorporating Prussian blue (PB) with porous gold nanoparticles ( p ‐Au NPs). Due to their rich built‐in Raman hotspots, the p ‐Au NPs are excellent SERS substrates that can significantly amplify the signals of the incorporated PB. In parallel, PB shows a single peak in the cellular silent region, where the signals from the probes and endogenous molecules can be completely resolved without the need of complex spectral unmixing. As a consequence, the combination of probe signal enhancement and background elimination endows the SERS probes with an extremely high SBR. To evaluate their performance in biomarker imaging, the high‐SBR SERS probes are utilized to profile folic acids at a single‐cell level. This background‐free, high‐precision imaging technique is conducive to early diagnosis and therapeutic response of cancer that is of great importance in clinical settings. Abstract : A high signal‐to‐background surface‐enhanced Raman scattering (SERS) probe for profiling cellular biomarkers without the interference of endogenous signals is presented. The p ‐Au nanoparticles are excellent SERS substrates that can significantly amplify the signals of the incorporated Prussian blue (PB), meanwhile, PB shows a single peak in the cellular silent region. Consequently, this methodology could facilitate to profile trace biomarkers of interest accurately.